Observations of Upwelling and Downwelling Around Antarctica Mediated by Sea Ice - Ramadhan, Ali; Marshall, John; Meneghello, Gianluca; Illari, Lodovica; Speer, Kevin (Frontiers in Marine Science, 2022)
We infer circumpolar maps of stress imparted to the ocean by the wind, mediated by sea-ice, in and around the Seasonal Ice Zone (SIZ) of Antarctica. In the open ocean we compute the wind stress using surface winds from daily atmospheric reanalyses and applying bulk formulae. In the presence of sea ice, the stress imparted to the underlying ocean is computed from satellite observations of daily ice concentration and drift velocity assuming, first, that the ocean beneath is not moving, and then including surface geostrophic ocean currents inferred from satellite altimetry. In this way global maps of surface ocean stress in the SIZ are obtained. The maps are discussed and interpreted, and their importance in setting the circulation emphasised. Just as in parallel observational studies in the Arctic, we find that ocean currents significantly modify the stress field, the sense of the surface ageostrophic flow and thus pathways of exchange across the SIZ. Maps of Ekman pumping reveal broad patterns of upwelling within the SIZ which are offset by strong narrow downwelling regions adjacent to the Antarctic continent.